The changing role of U.S. corporate research labs - Corcoran, Elizabeth (Research management (Now: research technology management))
Elizabeth Corcoran samples the spectrum of redirection, from contracting with business units at GE, Alcoa and elsewhere to provoking "exploratory learning" at Xerox.